Bahan Ajar Matrikulasi Pendidikan Bahasa Arab - Samin, Saproni Muhammad (UIR Press, 2020)
The purpose of this research is to find out the essential educational competencies that must be understood by new students which are the demands of the curriculum on Education of Arabic Language of Universitas Islam Riau (UIR) and determine matriculation learning materials. This research used the Qualitative Research Method within photographic technique functioned as initial research to collect data to create the education framework of learning material mapping. Data collection technique is done through literature study and interviews on to lecturers in language skill courses in Education of Arabic Language of UIR with a total of 5 people. This research concluded the learning materials in matriculation for Education of Arabic Language of UIR can be formulated into a package of methods presented in the form of 8 (eight) practical steps.